Schwinger pair production and string breaking in non-Abelian gauge theory from real-time lattice improved Hamiltonians - Spitz, Daniel; Berges, Jürgen (Physical review, 2019)
Far-from-equilibrium dynamics of SUo2thorn gauge theory with Wilson fermions is studied in 1 thorn 1 spacetime dimensions using a real-time lattice approach. Lattice improved Hamiltonians are shown to be very efficient in simulating Schwinger pair creation and emergent phenomena such as plasma oscillations. As a consequence, significantly smaller lattices can be employed to approach continuum physics in the infinitevolume limit as compared to unimproved implementations. This allows us to compute also higher-order correlation functions including four fermion fields, which give unprecedented insights into the real-time dynamics of the fragmentation process of strings between fermions and antifermions.
Gesehen am 08.04.2019